Translation of the 12-step alcoholic anonymous from English language to Yoruba language and its application within the Yoruba culture among patients with alcohol use disorder in Nigeria - Lasebikan, Victor Olufolahan (Mental health, religion & culture, 2017)
The aims of this study were to translate the English version of the 12-step alcoholic anonymous (AA) to the Yoruba version and to compare among patients with alcohol use disorders (AUDs), which version would be associated with a higher participation in AA. After an initial translation of the English version of the AA to Yoruba version, 200 participants with AUDs were randomised into either group, matched by age and gender and enrolled in the 12-step programme for six months. Compared to the Yoruba group, the proportion of participants retained in treatment in the English AA group was significantly lower between baseline and at six months, OR = .45, 95% CI (.26-.83). The Yoruba 12-step AA has the potential of mitigating the language barrier the English version poses to individuals with limited ability in the English language because participants felt more connected with God.